Two- and three-phase simulations of an ill-functioning dissolved-air flotation tank. (26th September 2011) - Emmanouil, Vasiliki A.; Karapantsios, Thodoris D.; Matis, Kostas A.
Computational Fluid Dynamics (CFD) simulations were employed to examine the performance of a large-scale Dissolved-Air Flotation (DAF) tank. The tank was ill-functioning as it was operated with bubbles larger than designed for. Different multiphase models, turbulence models and boundary conditions for the free surface of the tank were tested in 2D simulations. The simulation results were assessed through comparisons of the predicted spatial distributions of water velocity, volume fraction of air bubbles, solid particles and bubble/particles aggregates inside the tank. Comparisons revealed interesting similarities and differences between the examined models which were discussed as regards computational convenience and prediction goodness.